2002
DOI: 10.1209/epl/i2002-00256-8
|View full text |Cite
|
Sign up to set email alerts
|

Structure of polyelectrolytes in poor solvent

Abstract: PACS. 61.25.Hq -Macromolecular and polymer solutions. PACS. 36.20.Ey -Polymer molecules -conformation. PACS. 87.15Aa -Theory and modeling; computer simulation.Abstract. -We present molecular dynamics simulations on strongly charged polyelectrolytes in poor solvent. The resulting pearl-necklace conformations are analyzed in detail. Fluctuations in the number of pearls and their sizes lead only to small signatures in the form factor and the force-extension relation, which is a severe obstacle for experimental ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 35 publications
9
80
1
Order By: Relevance
“…Molecular dynamics simulations of partially charged polyelectrolytes with explicit counterions in poor solvent conditions were performed by the Mainz group [39][40][41][42] and by Liao et al [43]. These simulations have confirmed that polyelectrolyte chains at low polymer concentrations form necklaces of beads connected by strings (see Fig.…”
Section: Poor Solvent Conditions For the Polymer Backbonementioning
confidence: 92%
“…Molecular dynamics simulations of partially charged polyelectrolytes with explicit counterions in poor solvent conditions were performed by the Mainz group [39][40][41][42] and by Liao et al [43]. These simulations have confirmed that polyelectrolyte chains at low polymer concentrations form necklaces of beads connected by strings (see Fig.…”
Section: Poor Solvent Conditions For the Polymer Backbonementioning
confidence: 92%
“…For the most intriguing one, a pearl‐necklace ‐like shape of the chains, theoretical models for weakly41–43 and strongly44–47 charged chains have been developed. Computer simulation studies47–53 were successful in proving the existence of such conformations within single PE chain systems, providing valuable insight into their basic properties. Although the theory was developed for single chains, similar conformations of strands within the gel can be expected for a PE gel under poor‐solvent conditions24 where the scaling predictions change due to the network topology.…”
Section: Introductionmentioning
confidence: 99%
“…Such issues as approaching the thermodynamic limit ͑if it exists at all͒, finite size effects, properties of more concentrated polyelectrolyte solutions, and the effect of solvent quality on charged chains, 36,37 are still open and attractive for future research. Such issues as approaching the thermodynamic limit ͑if it exists at all͒, finite size effects, properties of more concentrated polyelectrolyte solutions, and the effect of solvent quality on charged chains, 36,37 are still open and attractive for future research.…”
Section: Discussionmentioning
confidence: 99%